2001
DOI: 10.1038/sj.bjp.0703950
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo‐oxygenase and lipoxygenase pathways in mast cell dependent‐neurogenic inflammation induced by electrical stimulation of the rat saphenous nerve

Abstract: 1 We investigated the role of arachidonic acid metabolism and assessed the participation of mast cells and leukocytes in neurogenic in¯ammation in rat paw skin. We compared the eect of lipoxygenase (LOX) and cyclo-oxygenase (COX) inhibitors on oedema induced by saphenous nerve stimulation, substance P (SP), and compound 48/80. 2 Intravenous (i.v.) pre-treatment with a dual COX/LOX inhibitor (RWJ 63556), a dual LOX inhibitor/cysteinyl-leukotriene (CysLt) receptor antagonist (Rev 5901), a LOX inhibitor (AA 861),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Furthermore, neurogenically-generated mediators such as substance P and other inflammatory mediators may also degranulate the mast cells (Matsuda et al 1989), thus creating a bidirectional positive feedback-loop. The mast cell stabilizer, cromolyn, inhibits nociceptive behavior in the second phase of the formalin test (Parada et al 2001) and electrical stimulation of the saphenous nerve-induced neurogenic inflammation (Le Filliatre et al 2001). The degranulation of mast cells in close proximity to the nerves innervating the colonic mucosa is correlated with abdominal pain in IBS patients (Barbara et al 2004).…”
Section: Nociceptionmentioning
confidence: 98%
“…Furthermore, neurogenically-generated mediators such as substance P and other inflammatory mediators may also degranulate the mast cells (Matsuda et al 1989), thus creating a bidirectional positive feedback-loop. The mast cell stabilizer, cromolyn, inhibits nociceptive behavior in the second phase of the formalin test (Parada et al 2001) and electrical stimulation of the saphenous nerve-induced neurogenic inflammation (Le Filliatre et al 2001). The degranulation of mast cells in close proximity to the nerves innervating the colonic mucosa is correlated with abdominal pain in IBS patients (Barbara et al 2004).…”
Section: Nociceptionmentioning
confidence: 98%
“…via marginal ear vein to rabbits 60 min prior to i.d. toxin injections as described above (33,35). Celecoxib (75 mg/kg/day) was mixed with 2 ml of Nutri-Cal (Evsco Pharmaceuticals, Buena, NJ), a veterinary nutritional supplement containing 34.5% fat, to facilitate oral administration (64).…”
Section: Methodsmentioning
confidence: 99%
“…This involves the activation of endothelial cells increasing the gaps between them resulting in leakage of plasma and proteins causing edema. Increased substance P following nerve injury also leads to the activation of mast cells causing an increase in the release of histamine, leukotrines and prostagalandins (Le Filliatre et al, 2001). The association of mast cells and fibrosis has long been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Studies had demonstrated the role of mast cell activation in the development of neurogenic edema and inflammation (Le Filliatre et al, 2001). Accumulating evidences showed that following nerve injury, the upregulation of substance P participate in the development of neuropathic pain and inflammation (Chen et al, 2015;Teodoro et al, 2013).…”
Section: Discussionmentioning
confidence: 98%